Modeling Fertilizer Demand in Cotton-Producing Villages of Benin: Does Price Matter in a Centralized Distribution System? - Honfoga, Barthelemy G. (European Scientific Journal, ESJ, 2016)
Cotton is a strategic crop in Benin’s economy and fertilizer is a crucial necessity for its development. Fertilizer supply is awkwardly cotton-oriented and depends totally on imports. Spurious liberalization, characterized by partial state withdrawal combined with a rigid distribution agreement between the state, fertilizer traders and farmersâ€™ cooperatives, led to a drastic decline in fertilizer use and cotton production. Although fertilizer consumption resumed timidly with reforms, the supply system remained centralized (importersâ€™ licensing, distribution quotas, price administration). This study inquired whether price is relevant in fertilizer demand in such a business environment. Randomly-selected 577 cotton farmers from purposively-chosen 191 cotton-producing villages, were interviewed about fertilizer use and distribution using structured questionnaires. Determinants of average villagelevel fertilizer demand, elicited using a multiple regression model with a joint agronomic and marketing perspective, included at 5% or 1% significance level: the regionâ€™s dummy, share of cotton in cultivated area, rural roadsâ€™ density, distance â€˜village store - farmerâ€™s fields, and off-farm income. Other non-negligible factors included: estimated cost price, soil degradation rate, diffusion rate of water and soil conservation techniques, proportion of leased land area and distance â€˜farmerâ€™s house - local agricultural marketâ€™. Despite an administered pan-territorial district-level price, fertilizer demand was still sensitive to the actual farm-gate prices. However, the business environment had a stronger influence. The policy levers to increase fertilizer use intensity include the development of road and market infrastructures, promotion of market orientation of farming and off-farm activities, wise liberalization of fertilizer retail market, and reform of the licensing system.